Einige Bemerkungen zu den Liefergebieten und Sedimentationsräumen der Lösse im Raum Marburg/Lahn auf Grund tonmineralogischer Untersuchungen - Heine, Klaus (ERDKUNDE, 1970)
X-ray diagrams and electron microscope prints of the clay fractions of various Würm loesses in the Marburg area show surprising differences with regard to the set of clay minerals which could not be solely caused by pedochemical processes after loess accumulation, but must be attributed to processes operating in different source areas. An impor tant part of the loess material was blown out in close proximity to the region of deposition. Qualitative diffe rences in clay mineral linkages indicate the following main source areas: the loesses on the eastern edge of the Rhine Massif come from the slopes of the massif and the gravel floors of the streams debouching from the mountains; the loesses of the middle Lahn valley were blown out of the Lahn gravels; the loess material of the northern Amöneburg Basin comes largely from the gravels of the Ohmtal Depression, and the loesses of the southern Amöneburg Basin were blown from the lower Vogelsberg and from the valleys of nearby rivers and streams. A comparison of the results of the loess investigations with those of various flood plain silts confirms the view that the blowing out and accumulation of the loesses must have taken place within a very small area.